GAYA PENGASUHAN ORANGTUA DENGAN PERILAKU BERMASALAH PADA ANAK TAMAN KANAK-KANAK (TK) - Amadhea Septining Tyas; Agnes Maria Sumargi (Universitas Katolik Widya Mandala Surabaya, 2019)
Young children usually show emotional and behavioural problems, such as fighting and aggression, and showing anxiety. Parenting style is one of the factors that influence behavioural problems. Theoretically, parenting style is divided into authoritative, authoritarian, and permissive parenting. Authoritarian and permissive parenting influence children in a negative way, while authoritative parenting influences children in a positive way. Studies regarding the impact of parenting style on young children’s emotional and behavioural problems are limited; therefore, the purpose of this study was to examine the relationship between parenting styles and behavioural problems of kindergarten students. Participants were 71 parents of children at kindergarten X and Y in Surabaya. Parents completed parenting and child behavior measures, i.e. Parenting Style and Dimension Questionnaire (PSDQ) to measure parenting style and Strength and Difficulties Questionnaire (SDQ) to measure child emotional and behavioral problems. Results showed a correlation coefficient of -0,049, p = 0,563 (p > 0,05) for authoritative parenting and child emotional and behavioural problems, a correlation coefficient of 0,336, p = 0,000 (p < 0,05) for authoritarian parenting and child emotional and behavioural problems, and a correlation coefficient of 0,267, p = 0,002 (p